Mesospheric front observations by the OH airglow imager carried out at Ferraz Station on King George Island, Antarctic Peninsula, in 2011 - G. A. Giongo; J. V. Bageston; P. P. Batista; C. M. Wrasse; G. D. Bittencourt; I. Paulino; N. M. Paes Leme; D. C. Fritts; D. Janches; W. Hocking; N. J. Schuch (Annales Geophysicae, 2018)
The main goals of this work are to characterize and investigate the potential wave sources of four mesospheric fronts identified in the hydroxyl near-infrared (OH-NIR) airglow images, obtained with an all-sky airglow imager installed at Comandante Ferraz Antarctic Station (EACF, as per its Portuguese acronym) located on King George Island in the Antarctic Peninsula. We identified and analyzed four mesospheric fronts in 2011 over King George Island. In addition, we investigate the atmospheric background environment between 80 and 100 km altitude and discuss the ducts and propagation conditions for these waves. For that, we used wind data obtained from a meteor radar operated at EACF and temperature data obtained from the TIMED/SABER satellite. The vertical wavenumber squared, m 2 , was calculated for each of the four waves. Even though no clearly defined duct (indicated by positive values of m 2 sandwiched between layers above and below with m 2 < 0) was found in any of the events, favorable propagation conditions for horizontal propagation of the fronts were found in three cases. In the fourth case, the wave front did not find any duct support and it appeared to dissipate near the zenith, transferring energy and momentum to the medium and, consequently, accelerating the wind in the wave propagation direction (near to south) above the OH peak (88–92 km). The likely wave sources for these four cases were investigated by using meteorological satellite images and in two cases we could find that strong instabilities were potential sources, i.e., a cyclonic activity and a large convective cloud cell. In the other two cases it was not possible to associate troposphere sources as potential candidates for the generation of such wave fronts observed in the mesosphere and secondary wave sources were attributed to these cases.